Timeline of COVID-19 in Tokyo and New Zealand: What will be Important and Can be Applied to Tokyo - Dashnyam Lkhagvasuren; Inomata Haruki; Iwashiro Eito; Iuchi Shoki; Uchida Marina; Iwata Kazuya; Imaya Kohei; Le Hoa Duyen; Thaingi Hlaing; LE Tran Ngoan (Asian Pacific Journal of Environment and Cancer, 2020)
Background: Although Japan is a country with a very low number of COVID-19 related death, the number of cases has been increasing steadily. Currently Japan’s metropolis Tokyo has the most number of confirmed COVID-19 cases of 7,927, roughly 36% of the total number nationwide by 13 July 2020. In this article, we analyzed the COVID-19 cases in Tokyo, concerning its time trend and compare it with those of New Zealand. Aims: By comparing the time trend of COVID-19 cases in Tokyo with that of New Zealand, we aim to point out what will be important and can be applied to Tokyo. Methods and Material: We used the database of daily registration and publication of confirmed cases of COVID-19 by the New Zealand Ministry of Health (1,544 patients), and metropolis Tokyo Government (7,927 patients) by 13 July 2020. Characteristics of confirmed cases include case ID, age, sex, import, and local transmission cases. The daily number of positive cases during these 171 days in both Tokyo and New Zealand was presented in Figure to compare the occurrence COVID-19 between two populations. Results: The main characteristics of Tokyo COVID-19 cases is that it has two waves, and the fact that most of them are locally acquired cases. Even though in May, Tokyo has experienced a dip, starting from July cases have started to increase again with the record of 243 daily new cases on July 10th, 2020. In contrast, during the last 51 days, from 23 May to 12 Jul. 2020, there were no locally positive cases in the country in New Zealand. Conclusions: Early detection of a possible incidence and suspected case, testing, tracing, self-care of each individual as well as strict isolation is recommended to control the COVID-19 infection for the next wave of infections.